A bis-benzimidazole PMO ratiometric fluorescence sensor exhibiting AIEE and ESIPT for sensitive detection of Cu2+. Issue 24 (2nd May 2019) - Hao, Xiafan; Han, Shuhua; Zhu, Jingtao; Hu, Yongfeng; Chang, Lo Yueh; Pao, Chih-Wen; Chen, Jeng-Lung; Chen, Jin-Ming; Haw, Shu-Chih
Abstract : A novel bis-benzimidazole organic siloxane precursor (BBM-Si) was prepared, and was combined with tetraethylorthosilicate (TEOS) as a mixed Si source. Abstract : A novel bis-benzimidazole organic siloxane precursor (BBM-Si) was prepared, and was combined with tetraethylorthosilicate (TEOS) as a mixed Si source. Then, bridged periodic mesoporous organosilica (BBM-PMO) spherical nanoparticles were synthesized by co-condensation using cetyltrimethylammonium bromide (CTAB) as structure directing agent. The optical properties showed that BBM qualifies as an "aggregation induced emission enhanced" (AIEE) molecule, exhibiting characteristics of excited-state intramolecular proton transfer (ESIPT), such as a large Stokes shift and dual fluorescence emission. For the BBM-PMO materials, the silica skeleton provides a rigid environment that limits molecular rotation, resulting in improved fluorescence emission. In particular, the BBM-PMOs exhibited dual emission of the enol and keto forms, achieving a ratiometric response to Cu 2+ with high sensitivity and selectivity in a broad pH range. Additionally, the limit of detection was as low as 7.15 × 10 −9 M in aqueous solution. The X-ray absorption near-edge spectroscopy (XANES) showed the coordination structure through the interaction between copper ions and N atoms of benzimidazole in the BBM-PMO coordinated to Cu 2+ . These results demonstrate that BBM-PMO hybrid materials have potential applications in the fields of bio-imaging and environmental monitoring.